Prevalence and Determinants of Painful and Painless Neuropathy in Type 1 Diabetes Mellitus - Barbosa, Margarida; Saavedra, Ana; Oliveira, Sofia; Reis, Ligia; Rodrigues, Filipa; Severo, Milton; Sittl, Reinhard; Maier, Christoph; Carvalho, Davide M. (Frontiers in Endocrinology, 2019)
Aims: To evaluate (1) the prevalence of diabetic distal symmetrical sensory-motor polyneuropathy (DSPN) and painful DSPN among patients with type 1 diabetes mellitus (DM1) aged over 18 years and (2) the determinant factors of neuropathy and pain in those patients.
CRIS-Team WoS Importer:2019-07-16